Kemampuan Berbahasa pada Pasien Narkoba di Rehabilitasi Islami Ujung Batu Kabupaten Rokan Hulu - Asih Ria Ningsih; Nuratika Nuratika; Misra Nofrita; Lita Syahrini; Rosinda Rosinda (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the language abilities of drug patients undergoing rehabilitation at the Islamic Rehabilitation Center in Ujung Batu, Rokan Hulu Regency. Rehabilitation is one of the efforts to support the physical and mental recovery of drug users, where one important aspect that needs attention is communication ability. The method used in this study is descriptive qualitative, employing in-depth interviews with the patients. The findings indicate a total of 30 data points categorized into three aspects of language production in drug patients: 22 instances of conceptualization, 5 instances of formulation, and 3 instances of articulation. It can be concluded that drug addicts experience communication failures in language production due to disturbances in the brain’s nervous system.